Penerapan Teknologi Tepat Guna “Alat Pendeteksi Kesuburan Tanah” di Desa Balonggebang - Deni Firmansyah; Nugik Rian Muhrozim; Jeremias Putra Axel Sidabutar; Nurul Avina Amalia; Alvian Dwi Sanjaya (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
Indonesia has earned the nickname as an "agrarian" country, this is because most of the population works as farmers. This nickname is very suitable for the situation in several regions in Indonesia, one of which is in Nganjuk Regency, namely in the village of Balonggebang. Balonggebang Village is the largest village in Gondang District, Nganjuk Regency. This village has a large enough agricultural land so that the majority of Balonggebang villagers work as farmers and the main commodities are rice and shallots. The first determining factor is the level of soil fertility. To determine whether the soil is fertile or not, it can be seen by using a soil fertility meter. In this modern era, soil fertility determination tools can be made simply and can be used as appropriate technology.